Antibiogram Profile of Respiratory Pathogens and Identifying Predisposing Factors of Respiratory Tract Infections among Patients Visiting Bhaktapur Hospital (Tribhuvan University Journal of Microbiology, 2024)
Objectives: To address the current problem of MDR infections and respiratory bacterial pathogens and identify the risk factors associated with respiratory tract infections (RTIs).Methods: A total of 327 RTI specimens were cultured using a conventional microbiological method to identify potential bacterial pathogens. The isolates were then subjected to antibiotic susceptibility testing using modified Kirby Bauer’s disc diffusion method. In addition, the risk factors associated with RTIs were obtained by direct interviews with patients using a structured questionnaire.Results: The overall prevalence of RTIs among the study population was found to be 11.9%. The highest rate of infections was observed among patients of age group 61-70 years in both sexes and from ICU wards. Among the bacterial pathogens, Acinetobacter baumannii was isolated in the highest number followed by Pseudomonas aeruginosa. 64.2% A. baumannii isolates were resistant to Azithromycin but 100% sensitive to meropenem. P. aeruginosa resistance rate was 50% to Piperacillin-tazobactam, ciprofloxacin, Polymyxin B and Ceftriaxone, and had the highest MDR. Half of the Staphylococcus aureus isolates were MRSA. Risk factors such as previous infections, family history with RTIs, chronic use of antibiotics, and smoking were found to be significantly associated with RTIs.Conclusion: We observed high MDR among the respiratory pathogens with growing resistance to β-lactam, macrolides, and Polymyxins whch necessitates alternative drugs in management. There is also need for targeted preventive strategies, prohibition of irrational use of antibiotics, and avoidance of exposure to risk factors such as smoking, outdoor air pollution, and chronic use of antibiotics.